Grace: The Stream of Divine Life for Man in the Bhakti Traditions - Thomas Manickam (Journal of Dharma, 1987)
of human life is central to the Bhakti traditions in India. Prasada meaning "grace", "benediction," "benevolence", "graciousness", "tenderness", "kindness". "righteousness", "blessing" etc. of God, visualised in a personal form, occurs as a very common expression in the Bhakti traditions of India, and so documented in some of the Upanishads, Bhagavadgita and Ramayana in the Sanskrit lineage on the one hand. and in the Saiva Siddhanta and the Vaishnavite Agarnas of the Tamil lineage on the other. These are two major channels of Bhakti traditions in the Aryan and Dravidian cultural milieux respectively. Also there are other expressions like day-i, meaning "mercy", "gift", "benevolence" derived from the root dii, and krupa from krp, meaning "benediction", "good pleasure", "blessing" "grace" as well as karunii meaning "forgiveness", "compassion", "sympathy", righteousness" etc. Anugraha -"benediction", "good pleasure", "guidance", "assistance", "protection" - is also found frequently used in the Sanskrit tradition to represent the stream of the divine life offered to mankind for support, sustenance, sanctification and final liberation. In the Tamil tradition arul means all these and in Malaya lam linguistic lineage of the Dravidian recension varaprasiidam or prasiidavaram in the mutually convertible composite form is often used to mean practically all the above said meanings. The gratuitous character (gift dimension) of Grace is especially connoted by the word varaprasiidam or prasiidavaram used the Christian Bhakti traditions of the Dravidian lineage of Indian Culture. mostly prevalent in Kerala. Man is constantly supported by the grace (prasada) of a benevolent God who behaves like a benevolent Master, Guru, who leads his disciples to the achievement of the ultimate goal of human life, namely, spiritual liberation which is a communion with Himself, livable in this phase of life and to be continued in its perfection to the life beyond This is said to be life divine, the life lead by the grace of God.